(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
The article provides theoretical justification for the importance of physical exercise for human life and health, the personal routine of schoolchildren, hygienic rules for engaging in physical exercise, the rules and requirements for performing gymnastic exercises before classes in the morning, and procedures for preventing injuries when performing physical exercises in the subject "Physical Education". It also covers the principles of proper nutrition, homework and physical education minutes, requirements for independent performance of URM exercises, and the negative impact of harmful habits on human health.